2007
DOI: 10.1016/j.susc.2007.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Water adsorption and dissociation on BeO(001) and (100) surfaces

Abstract: Plateaus in water adsorption isotherms on hydroxylated BeO surfaces suggest significant differences between the hydroxylated (100) and (001) surface structures and reactivities. Density functional theory structures and energies clarify these differences. Using relaxed surface energies, a Wulff construction yields a prism crystal shape exposing long (100) sides and much smaller (001) faces. This is consistent with the BeO prisms observed when beryllium metal is oxidized. A water oxygen atom binds to a single su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 41 publications
(59 reference statements)
0
13
0
Order By: Relevance
“…Members of our team have performed theoretical studies on the different surfaces of BeO that show the exposed surface face can influence the thermodynamics significantly. 42 These studies show that the (0 0 1) face of BeO has the greatest reactivity in water, and becomes hydroxylated during the reaction. (Fig.…”
Section: Inhalation and Dissolutionmentioning
confidence: 97%
“…Members of our team have performed theoretical studies on the different surfaces of BeO that show the exposed surface face can influence the thermodynamics significantly. 42 These studies show that the (0 0 1) face of BeO has the greatest reactivity in water, and becomes hydroxylated during the reaction. (Fig.…”
Section: Inhalation and Dissolutionmentioning
confidence: 97%
“…45,52 The presence of atomic hydrogen and hydroxyl groups on the initially oxidized Be(0001) surface is likely due to the dissociation of residual H 2 O. 6,53 In Ref. 6 it has been shown that H dissociated from H 2 O is trapped in the oxide layer.…”
Section: B Acoustic Surface Plasmonmentioning
confidence: 99%
“…5,6 And correspondingly, the adsorption and dissociation of many gases such as H 2 O, O 2 and H 2 have already been studied academically. [7][8][9][10] Considering the usages of Be surfaces and the requirements of automotive catalytic converters, a systematic study of the adsorption and dissociation of N 2 molecules on the Be surfaces is obviously needed.…”
Section: Introductionmentioning
confidence: 99%